HPLC Stability Indicating Assay Method for Metformin Hydrochloride in Bulk Drug and Tablets and Cytotoxicity of Degradation Products - Cristina Stenger, Fernanda; Catia Block, Luciana; Correa, Rogerio; Alves de Freitas, Rilton; Mari Belle Bresolin, Tania (Current Pharmaceutical Analysis, 2012)
The present work reports a stability-indicating reversed phase ion pair liquid chromatography method for quantitative determination of metformin hydrochloride (MTF) (drug and tablets) and assessment of the cytotoxicity of degraded MTF. Chromatographic separation was performed on a C18 (Phenomenex® Luna), 5.0 μm (250 mm x 4.6 mm) column using isocratic elution. The optimized mobile phase consisted of 10 mmol L-1 heptane sulphonic acid (pH 3.0), acetonitrile and methanol (75:8:17 v/v), flow 1.0 mL.min-1, at 30 ºC. The eluted compounds were monitored at 210 nm wavelength using a DAD detector. The stability indicating capability of the developed method was established by analyzing forced degradation samples (acid, alkali, neutral, oxidative and photolytic condition) in which the spectral purity of MTF was ascertained, along with the separation of degradation products from the analyte peak. The cytotoxicity of MTF and the degraded drug was analyzed in the L929 cell test by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay. The 500 mg of commercial MTF tablets (Reference, Generic and Similar drugs) showed a similar chromatographic profile, but lower intensity degradation in the same conditions, in relation to the bulk drug in almost forced conditions. Neither the degraded drug samples, nor the tablet samples degraded in acid conditions, showed any cytotoxicity. The developed stability-indicating ion-pair HPLC method was fully validated according to the International Conference on Harmonization (ICH) guidelines. The degraded sample of MTF showed no affect on cell viability, compared with the non-degraded drug.
Keywords: Metformin hydrochloride